Sponge community of the western Black Sea shallow water caves: diversity and spatial distribution - Ereskovsky,Alexander; Kovtun,Oleg A.; Pronin,Konstantin K.; Apostolov,Apostol; Erpenbeck,Dirk; Ivanenko,Viatcheslav (PeerJ, 2018)
Marine caves possess unique biocoenotic and ecological characteristics. Sessile benthic species such as sponges associated with cave habitats typically show a marked zonation from the cave entrance towards the end of the cave. We describe three semi-submerged karstic caves of 50 to 83 m length and 936 to 2,291 m3 volume from the poorly explored cavernicolous fauna of North-East Bulgaria. We surveyed sponge diversity and spatial variability. Eight demosponge species were identified based on morphological and molecular data, of which six are known from the adjacent open sea waters of the Black Sea. Two species, Protosuberites denhartogi van Soest & de Kluijver, 2003 and Halichondria bowerbanki Burton, 1930, are reported from the Black Sea for the first time. The spatial sponge distribution inside the caves is in general similar, but shows some differences in species composition and distribution depending on cave relief and hydrodynamics. The species composition of sponges of Bulgarian caves is found to be different from Crimean caves. An updated checklist of the Black Sea sponges is provided.
Keywords: Bulgaria; The Black Sea; Porifera; Marine caves; Checklist; Karst cave habitat; Extreme environment; Inventory; Cave-dwelling fauna